2018
DOI: 10.1113/jp275810
|View full text |Cite
|
Sign up to set email alerts
|

Effects of living at moderate altitude on pulmonary vascular function and exercise capacity in mice with sickle cell anaemia

Abstract: Exposure to high altitude worsens symptoms and crises in patients with sickle cell disease (SCD). However, it remains unclear whether prolonged exposure to low barometric pressures exacerbates SCD aetiologies or impairs quality of life. We tested the hypothesis that, relative to wild-type (WT) mice, Berkley sickle cell mice (BERK-SS) residing at sea level, mild (1609 m) and moderate (2438 m) altitude would have a higher rate of haemolysis, impaired cardiac function and reduced exercise tolerance, and that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Transgenic murine models of SCA (Berk-ss) expressing human α and β S globin 24 26 exhibit multi-organ pathologies that manifest spontaneously and include hemolysis resulting in severe anemia, iron accumulation (splenic, hepatic, renal, and pulmonary) and cardiopulmonary abnormalities that approximate homozygous disease in humans. 24 26 Deletion of both β minor and β major genes on one beta globin allele and the other normal define the β-thalassemia intermedia mice (Hbb th3/+ ) that demonstrate mild anemia, splenomegaly, and iron accumulation in all organs. 7 , 27 We report extensive iron-loaded macrophages in remodeled human SCA-PH pulmonary vascular tissue and in rodent models of SCA-PH.…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic murine models of SCA (Berk-ss) expressing human α and β S globin 24 26 exhibit multi-organ pathologies that manifest spontaneously and include hemolysis resulting in severe anemia, iron accumulation (splenic, hepatic, renal, and pulmonary) and cardiopulmonary abnormalities that approximate homozygous disease in humans. 24 26 Deletion of both β minor and β major genes on one beta globin allele and the other normal define the β-thalassemia intermedia mice (Hbb th3/+ ) that demonstrate mild anemia, splenomegaly, and iron accumulation in all organs. 7 , 27 We report extensive iron-loaded macrophages in remodeled human SCA-PH pulmonary vascular tissue and in rodent models of SCA-PH.…”
Section: Introductionmentioning
confidence: 99%
“…This effect can also occur at the muscle level, so that Hp binds peripherally to free Hb, carrying it to the liver and limiting its prooxidative action in the muscle [ 8 ] ( Figure 1 ). Therefore, an increase in Hp in the blood may be related to a protective activity in muscles by preventing extravasation of free Hb in the skeletal muscle tissue, thus inhibiting O2 deficiency in the skeletal muscle tissue [ 14 ]. This prevents oxidative damage and would justify its role as an antioxidant molecule, as has already been demonstrated in previous studies [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the direct effects of free Hb on skeletal muscle vascular and metabolic function, it has recently been demonstrated that the Berkeley mouse model of SCD (BERK) exhibits impaired exercise tolerance due, at least in part, to right heart insufficiency and pulmonary hypertension linked to reduced NO bioavailability (22). A major strength of this previ-Correspondence: S. K. Ferguson (Scott.Ferguson@Hawaii.edu).…”
Section: Introductionmentioning
confidence: 99%